The Effect of Bitter Melon (Momordica charantia L.) Juice on Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - M Syikir Abdullah; Jurana Jurana; Yulia Citra; Tri Wulansari Dewi (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion or insulin resistance. In addition to pharmacological therapy, complementary treatments derived from natural products are increasingly explored to support glycemic control. Bitter melon (Momordica charantia L.) contains bioactive compounds with potential hypoglycemic effects. This study aimed to evaluate the effect of bitter melon juice on blood glucose levels among patients with type 2 diabetes mellitus in Madatte Village, Polewali District. A quasi-experimental study with a pre-test and post-test time-series design was conducted. Fifteen patients with type 2 diabetes mellitus were selected using consecutive sampling and received 200 grams of freshly prepared bitter melon juice once daily. Blood glucose levels were measured at baseline, after 3 days, and after 7 days of intervention using a glucometer. Data were analyzed using the Friedman test. The results demonstrated a gradual reduction in mean blood glucose levels from 194.60 mg/dL at baseline to 191.93 mg/dL after 3 days and 184.80 mg/dL after 7 days. Statistical analysis showed a significant difference in blood glucose levels across the measurement periods (p = 0.01; p < 0.05). In conclusion, daily consumption of bitter melon juice was associated with a significant reduction in blood glucose levels in patients with type 2 diabetes mellitus, with a more pronounced effect observed after seven days of intervention. Bitter melon juice may be considered a complementary approach for glycemic control.